Accordance of Adolescent and Parental Ratings of Internet Gaming Disorder and Their Associations with Psychosocial Aspects - Wartberg, Lutz; Zieglmeier, Matthias; Kammerl, Rudolf (Cyberpsychology Behavior and Social Networking, 2019)
In 2013, Internet gaming disorder (IGD) was incorporated in the DSM-5. In 2018, the World Health Organization (WHO) confirmed the inclusion of the new diagnosis “Gaming disorder” in the ICD-11. Both IGD and Gaming disorder refer to a problematic use of video games. Yet, IGD has thus far only been assessed by self-ratings, while external ratings have not been available. We adapted a frequently used screening tool for IGD (Internet Gaming Disorder Scale, IGDS) to a parental rating (Parental version of the Internet Gaming Disorder Scale, PIGDS) and evaluated its psychometric properties. Data were collected in 1,970 face-to-face interviews (with 985 parents and 985 related adolescents) using a standardized questionnaire measuring adolescent IGD by self- and parental ratings and frequency of gaming, psychopathological burden, hyperactivity/inattention, family functioning, and school performance. Furthermore, we determined the accordance of adolescent and parental ratings for IGD. We conducted a confirmatory factor analysis, correlation analyses, and have determined reliability and concordance. We observed a one-dimensional factor structure of the PIGDS and its internal consistency was 0.86. We found very first indications of criterion validity for the PIGDS. The correlation between IGDS and PIGDS was 0.78 and we observed kappa coefficients between both ratings of 0.62 and 0.61 (based on the most suitable cutoff points for the PIGDS). Both adolescent and parental ratings of IGD were consistently associated with higher psychopathological burden, stronger hyperactivity/inattention, poorer family functioning, and poorer school performance. According to the results, a parental assessment of IGD in adolescence seems to be a promising new approach and it opens a new perspective in the exploration of IGD.
Keywords: gaming disorder; internet addiction; adolescent; parent; assessment; questionaire

A longitudinal study on psychosocial causes and consequences of Internet gaming disorder in adolescence - Wartberg, Lutz; Kriston, Levente; Zieglmeier, Matthias; Lincoln, Tania; Kammerl, Rudolf (Psychological Medicine, 2018)
Background. In 2013, Internet gaming disorder (IGD) was incorporated in the current version of the DSM-5. IGD refers to a problematic use of video games. Longitudinal studies on the etiology of IGD are lacking. Furthermore, it is currently unclear to which extent associated psychopathological problems are causes or consequences of IGD. In the present survey, longitudinal associations between IGD and adolescent and parental mental health were investigated for the first time, as well as the temporal stability of IGD. Methods. In a cross-lagged panel design study, family dyads (adolescent with a parent each) were examined in 2016 (t1) and again 1 year later (2017, t2). Overall, 1095 family dyads were assessed at t1 and 985 dyads were re-assessed at t2 with standardized measures of IGD and several aspects of adolescent and parental mental health. Data were analyzed with structural equation modeling (SEM). Results. Male gender, a higher level of hyperactivity/inattention, self-esteem problems and IGD at t1 were predictors of IGD at t2. IGD at t1 was a predictor for adolescent emotional distress at t2. Overall, 357 out of the 985 adolescents received a diagnosis of IGD at t1 or t2: 142 (14.4%) at t1 and t2, 100 (10.2%) only at t1, and 115 (11.7%) only at t2. Conclusions. Hyperactivity/inattention and self-esteem problems seem to be important for the development of IGD. We found first empirical evidence that IGD could prospectively contribute to a deterioration of adolescent mental health. Only a subgroup of affected adolescents showed IGD consistently over 1 year.
Keywords: Adolescents; hyperactivity; Internet addiction; longitudinal analysis; psychopathology

An Empirical Exploration of Longitudinal Predictors for Problematic Internet Use and Problematic Gaming Behavior - Wartberg, Lutz; Zieglmeier, Matthias; Kammerl, Rudolf (Psychological Reports, 2020)
Problematic gaming (PG) has been included in the DSM-5 and ICD-11. But, it is still controversially discussed, if problematic (online-) gaming is a subtype of problematic Internet use (PIU) or if both behavior patterns should be distinguished. In joint samples, the relationships between PIU and PG and correlates have so far only been investigated in cross-sectional studies. This is the first longitudinal study to determine predictors of PIU, PG, and a combined occurrence of PIU and PG (PIU + PG) together in one sample. Overall, 985 family dyads (one parent and her/his child) were interviewed twice (at t1 and t2, with one year in between) with a standardized questionnaire regarding PIU, PG and psychosocial aspects. Predictors for adolescent PIU, PG, and PIU + PG were determined with a multinomial logistic regression analysis. The following were our findings: (a) PIU (t2) was predicted by stronger emotional distress (t1) and PIU (t1); (b) PG (t2) by male gender, more self-esteem problems (t1), stronger hyperactivity/inattention (t1), and PG (t1); and (c) PIU + PG (t2) by male gender, stronger hyperactivity/inattention (t1), and PG (t1). Partly different patterns of predictors were observed for the development of PIU and PG. The results indicate not only commonalities but also differences in the etiology of these behavior patterns.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Adolescent; etiology; gaming disorder; Internet addiction; longitudinal study; mental health; parent; predictor; psychopathology; video game

Diskussionsfelder der Medienpädagogik: Problematische Internetnutzung – Desiderat der Medienpädagogik - Kammerl, Rudolf; Zieglmeier, Matthias; Wartberg, Lutz (Handbuch Medienpädagogik, 2022)

Exzessive und problematische Internetnutzung im familialen Kontext - Kammerl, Rudolf; Zieglmeier, Matthias; Wartberg, Lutz (Kinder- und Jugendschutz in Wissenschaft und Praxis, 2019)
Keywords: Internetnutzung; exzessiv; problematisch; familialer Kontext

Kritische Perspektiven auf den Umfang der Internetnutzung Jugendlicher - Eine Frage der Generationszugehörigkeit? - Kammerl, Rudolf; Wartberg, Lutz; Zieglmeier, Matthias (Medienkritik im digitalen Zeitalter, 2018)
Kommunikation von Jugendlichen findet immer häufiger und länger über digitale Medien statt. In der vorliegenden Studie wurde die Übereinstimmung zwischen der subjektiven Adoleszenz (APP) und der elterlichen Problemwahrnehmung (PPP) der jugendlichen Internetnutzung untersucht. In 609 von 1095 Fällen (55,6%) beobachteten wir eine totale Übereinstimmung zwischen APP und PPP. Im Vergleich zu ihren Kindern bewerteten 406 Eltern (37,1%) die Internetnutzung ihres Kindes als problematischer. Umgekehrt beurteilen nur 80 Jugendliche (7,3%) ihre eigene Internetnutzung problematischer als ihre Eltern. Um ein Maß für weitere statistische Analysen zu generieren, berechneten wir für jede Familie die Differenz zwischen PPP und APP. In einem linearen Querschnittsregressionsmodell war eine problematische Internetnutzung im Selbsturteil der Jugendlichen (APIU) statistisch signifikant assoziiert mit männlichem Geschlecht, höherem Alter, alleinerziehendem Elternteil, niedrigerem Sozialstatus, einer niedrigeren Familienfunktion (basierend auf elterlichen und jugendlichen Bewertungen) und der Differenz zwischen PPP und APP. In einer Längsschnittregressionsanalyse wurde ein APIU ein Jahr später durch das männliche Geschlecht, niedrigere Familienfunktionen (Eltern- und Jugendlicheneinschätzungen) und den Unterschied zwischen PPP und APP vorhergesagt. Die Ergebnisse unterstützen die Entwicklung von Maßnahmen zur Beratung und Interventio
Keywords: VEIF; Internetnutzung; Jugendliche; Problemwahrnehmung

Kritische Perspektiven auf den Umfang der Internetnutzung Jugendlicher. Eine Frage der Generationszugehörigkeit? - Kammerl, Rudolf; Wartberg, Lutz; Zieglmeier, Matthias (Medienkritik im digitalen Zeitalter, 2018)

Motive der Nutzung des sozialen Netzwerks Facebook unter der Berücksichtigung der Wirkung auf das soziale Kapital wie Freundschaften und die Persönlichkeit bzw. Identität der Nutzer/innen. Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Soziologie. (Nicht veröffentlicht) - Zieglmeier, Matthias (2013)

Parental media education and familial aspects for problematic Internet use in adolescence - Kammerl, Rudolf; Zieglmeier, Matthias; Wartberg, Lutz (Zeitschrift für Erziehungswissenschaft, 2019)
The importance of parental mediation and familial aspects for problematic Internet use in adolescence was investigated mainly in cross-sectional surveys. Central objective of the study "Trajectories of excessive Internet use in families" (VEIF) was to analyze these relationships in a longitudinal approach. For this purpose, family dyads (an adolescent and a related legal guardian) were surveyed once a year at three measurement points (t1 to t3) with standardized questionnaires concerning parental Internet mediation, family functioning and adolescent problematic Internet use. Overall, at t1 1095 family dyads were examined. At t2 985 dyads and at t3 852 dyads could be re-assessed. The cross-sectional results showed the relevance of family functioning and parental mediation (e.g., more inconsistent parental mediation) for problematic Internet use. In multivariable longitudinal analyses poorer family functioning, lower restrictive mediation and stronger technical mediation predicted problematic Internet use in adolescents.
CRIS-Team WoS Importer:2019-12-17

Studiengebundene Internetnutzung aufgrund biografischer Entwicklung, eine qualitative Untersuchung zur studiengebundenen Internetnutzung als geplantes Verhalten aufgrund biografischer Entwicklung anhand der TPB. Friedrich-Alexander-Universität Erlangen-Nürnberg. Lehrstuhl für Erziehungswissenschaftlich-Empirische Bildungsforschung (Nicht veröffentlicht) - Zieglmeier, Matthias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)

Welche Themen haben die Videos? - Zieglmeier, Matthias (Empirische Exploration nichtkommerzieller Video-Tutorials im Internet Dokumentation eines Studentischen Forschungsprojektes, 2015)